Markov Modelling of Small Cell Base Station Sleep Strategies with Disaster and Repairable Server (Contemporary Mathematics, 2025)
A network of Base Station (BS) is required in order to function mobile phones and other mobile devices. A large number of BSs will be deployed in advanced networks namely Long-Term Evolution (LTE-A) to achieve high data rates which result in heavy energy usage in cellular networks. The energy consumption can be reduced by BS sleep strategy. A Markov model (MM) is proposed for the strategy with disaster and repairable server, as a system may encounter a disaster at any stage. The proposed model efficiently calculates the energy saving factor with disaster and the results shows that the amount of power saved in BS increases with the number of light sleep cycles. The expressions for steady-state probabilities (SSP) and transient probabilities are derived . Moreover for the proposed model, mean and variance are computed. Numerical illustration on energy saving factor with disaster is presented to show the effectiveness.
Keywords: long-term evolution advanced, disaster, markov model, standby, continuous time markov chain